Patología nasosinusal benigna en el adulto mayor - Nazar S., Rodolfo; Pardo J., Javiera (Revista Hospital Clínico Universidad de Chile, 2011)
Nasal symptoms are a major health problem for elderly people and affect their quality of life. Inflammatory conditions and influence of age on nasal physiology determine its pathogenesis. Changes of immune function, structural characteristics of nasal mucus and moisture, as well as alterations of mucociliary clearance and nasal air flow are present in these patients. Among the most prevalent diseases are sinonasal rhinitis, both allergic and non allergic, epistaxis, decreased olfactory function and rhinophyma, final stage of rosacea. Improving our understanding of the pathophysiology behind these disorders, allow us to make a proper assessment of these patients and develop effective therapies to give them proper solution, thus improving their quality of life.